Investigating multi-channel banking adoption in South Africa - Patel, Kunal (Department of Information Systems, 2023)
Multi-channel retail banking is a novel banking approach, one which encompasses traditional banking approaches as well as modern internet based banking innovations. South Africa (SA) has the potential market to ensure the success of alternative banking strategies, which in turn would lead to better quality banking services. This study is of importance to banks, providing them with a better understanding of the consumer's interaction within the banking environment. The main objective of the study is to investigate the adoption of multi-channel banking in SA and to develop a theory that explains this phenomenon. Identifying these factors may allow the banks to ultimately improve the quality and reach of services of the channels independently or collectively. This study is conducted within an interpretivist paradigm under the guidance of an inductive approach. The purpose of this combination is to allow for the exploration of the phenomenon through the use ~f semi-structured interviews to gather data from only individuals who had bank accounts. The gathered data was analysed employing the techniques available through grounded theory methodology. Numerous concepts evolved through the analysis of the data and through the open coding technique. The main results showed that the consumer's decision making process and their continual growth of knowledge were highly influenced by varying concepts such as their banking needs, received experiences, the associated costs, preference of channel, the associated convenience and the received satisfaction of the respective channels of choice. The decision making process included the categories of channel evaluation and channel choice. The concepts within these categories were determined as being highly influenced among the collection of identified concepts. With their choices changing as their circumstances changed the channels were not thought of as independent, but rather a collective from which the consumer could choose from. This demonstrates the existence of the phenomenon of multi-channel banking.